IMPLEMENTASI MANAJEMEN PEMASARAN PENDIDIKAN DALAM MEMBANGUN CITRA SEKOLAH DI KOTA TANGERANG - Supatmin, Supatmin; Fitriyani, Syabrina (Bhinneka Multidisiplin Journal, 2025)
This study aims to analyze the implementation of educational marketing management in building the school image in Tangerang City. The research uses a qualitative descriptive approach through interviews, observations, and document analysis. The findings reveal that effective educational marketing management enhances the school’s positive image among the community. The applied strategies include strengthening public communication, improving service quality, and utilizing digital media for promotion. Moreover, the principal’s strategic leadership plays a key role in creating synergy among teachers, students, and the community. A good school image is shaped not only by promotion but also by academic reputation, service quality, and harmonious relationships. This study emphasizes that educational marketing management is a crucial element in building public trust and enhancing institutional competitiveness in the modern educational landscape